New developments in vehicle dynamics, simulation, and suspension systems. - Society of Automotive Engineers; SAE International Congress & Exposition Detroit, Mich.) (1995. (Warrendale, PA Society of Automotive Engineers, 1995)
Papers presented at the International Congress and Exposition, Detroit, Michigan, February 27-March 2, 1995.
"SP-1074."
"Global mobility database."
"SAE/SP-95/1074"--T.p. verso.
"February 1995."
Keywords: Automobiles -- Dynamics -- Congresses; Automobiles -- Dynamics -- Simulation methods -- Congresses; Automobiles -- Springs and suspension -- Congresses